Belimumab for the treatment of recalcitrant cutaneous lupus. (July 2017) - Vashisht, P; Borghoff, K; O'Dell, J R; Hearth-Holmes, M
Background: Belimumab is a monoclonal antibody that reduces B lymphocyte survival by blocking the binding of soluble human B lymphocyte stimulator (BLyS) to its B cell receptors. The utility of belimumab for management of resistant systemic lupus erythematosus (SLE) skin manifestations has not been reported. We present our experience of using this novel molecule for the successful management of cutaneous lupus at our center. Methods: We studied five patients with significant SLE skin manifestations. All patients met 1997 American College of Rheumatology (ACR) SLE criteria and had failed multiple medications to control their skin disease. SLE disease activity indexes (SLEDAI), Cutaneous LE disease Area and Severity Index (CLASI) and patient's global assessment (PGA) were recorded before and 16 weeks after belimumab treatment. Belimumab was added to concomitant standard therapy. Results: All five patients demonstrated marked clinical improvement subsequent to belimumab treatment. The average time to clinical improvement after treatment initiation was 8–12 weeks. SLEDAI scores (median, range) improved in all the patients ((2, 2–6) to (0, 0–4); p = 0.025). PGA scores (median, range) were better in all patients ((3, 2–3) to (1, 0–1); p = 0.039). CLASI activity scores (median, range) improved dramatically in all patients ((17, 9–31) to (3, 2–14); p = 0.043). There was no worsening of the CLASI damage scores. The mean daily prednisone dose decreased significantly from 31 mg (±18.8) at baseline to 3 mg (± 2.7) ( p = 0.042). Conclusion: In this case series, the addition of belimumab to standard therapy improved the signs and symptoms of refractory cutaneous lupus. This is one of the first reports highlighting the potential utility of this medication for the treatment of severe skin involvement in SLE refractory to conventional therapies. Additional studies need to be performed to assess the use of belimumab in the treatment of cutaneous lupus.